2022
DOI: 10.1021/acssynbio.1c00620
|View full text |Cite
|
Sign up to set email alerts
|

RPA/CRISPR/Cas12a-Based On-Site and Rapid Nucleic Acid Detection of Toxoplasma gondii in the Environment

Abstract: Toxoplasma gondii is an opportunistic pathogen widely distributed within the world, poses a huge threat to human health, and causes significant economic losses to the livestock industry. Herein, we developed a portable one-pot detection of T. gondii by combining recombinase polymerase amplification (RPA) and a clustered regularly interspaced short palindromic repeats (CRISPR)/Cas12a system. A glass microfiber filter device used for the first step can efficiently extract T. gondii from lowconcentration samples.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…established a portable one-pot assay for Toxoplasma gondii using RPA-CRISPR/Cas2a with a lower limit of detection of 3.3Copes/μl. A portable suitcase was also designed to meet the needs of on-site detection ( Lei et al., 2022b ). RPA had been successfully applied to detect many parasites, but the application was not yet widespread.…”
Section: The Application Of Rpamentioning
confidence: 99%
“…established a portable one-pot assay for Toxoplasma gondii using RPA-CRISPR/Cas2a with a lower limit of detection of 3.3Copes/μl. A portable suitcase was also designed to meet the needs of on-site detection ( Lei et al., 2022b ). RPA had been successfully applied to detect many parasites, but the application was not yet widespread.…”
Section: The Application Of Rpamentioning
confidence: 99%
“…Driving a pair with different sgRNAs of Cas9 generates dsDNA with sticky ends, ligated to a hairpin-structure substrate, which subsequently generates a large number of short fragments that report the electrical signal of the detected DNA (Dai et al, 2020). Huang's team developed a dCas9-ECL probe for sensitive and single-base specific DNA detection with good resistance to nonspecific interference and a low false positive detection rate (Wu L. et al, 2022). This shows that electrochemical biosensors can modularize the circuitry with better programmability.…”
Section: Nucleic Acid Detection Strategies 231 Cas9-based Biosensors ...mentioning
confidence: 99%
“…Nevertheless, current research on non-nucleic acid targets is also of considerable interest. Many detection systems have developed, especially in the food and environmental fields, to detect pathogenic small molecules or parasites (Lei et al, 2022;You et al, 2022), or pathogens in agriculture (Jiao et al, 2022;Zhu et al, 2022).…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Toxoplasma gondii is a globally distributed protozoan parasite, causing life-threatening consequences in immunocompromised patients [ 140 ] as well as abortions and stillbirths in livestock [ 141 , 142 ]. In combination with RPA or RAA, CRISPR-Cas12a/Cas13a based methods have been reported for quick in-field detection of T. gondii [ 91 , 92 , 93 ]. The authors demonstrated that the RAA-Cas12a/Cas13a systems have advantages over conventional PCR-based method in terms of conveniency and sensitivity [ 92 , 93 ].…”
Section: Current Applications Of Crispr/cas-based Nucleic Acid Detect...mentioning
confidence: 99%
“…The authors demonstrated that the RAA-Cas12a/Cas13a systems have advantages over conventional PCR-based method in terms of conveniency and sensitivity [ 92 , 93 ]. In terms of reducing cross-contamination and cost, the RPA-CRISPR/Cas12a assay (single-tube strategy and 100 nM of Cas12a) is more advanced than the RAA-CRISPR/Cas12a assay (two separate processes and 800 nM of Cas12a) [ 91 ]. Applications of these novel methods potentially contribute to the control of toxoplasmosis in humans and animals.…”
Section: Current Applications Of Crispr/cas-based Nucleic Acid Detect...mentioning
confidence: 99%